Physical Activity and Sleep Quality in Adolescents and Young Adults: A Comprehensive Literature Review - Szatkowski, Michał; Kryszpin, Paulina; Kania-Bonicka, Zofia; Krajewska, Natasza; Michniak, Wiktor (Quality in Sport, 2026)
Background. Sleep disturbances represent an escalating public health crisis among adolescents and young adults undergoing intensive neurobiological and social transitions. Modern 24-hour movement guidelines emphasize physical activity (PA) to counteract sedentary patterns and excessive digital engagement. Aim. This review synthesizes empirical evidence regarding the relationship between PA and sleep quality in populations aged 10–25, exploring physiological impacts, psychological mediators, and lifestyle constraints. Material and methods. A comprehensive search across PubMed, Web of Science, Cochrane, Embase, and Google Scholar identified 23 primary peer-reviewed studies (RCTs, longitudinal, cross-sectional, and systematic reviews). Eligible studies paired quantifiable PA metrics with validated sleep tools like the Pittsburgh Sleep Quality Index (PSQI) or actigraphy. Results. Regular moderate-to-vigorous PA directly optimizes subjective sleep quality and objective sleep architecture, yielding a substantial intervention effect (SMD = -2.10). PA also operates through indirect pathways by alleviating academic stress and pre-sleep rumination. However, these benefits are heavily constrained by lifestyle factors; high recreational screen time (>2 hours/day) and poor nutrition significantly erode exercise's sleep-protective effects. Methodologically, a dichotomy exists between subjective scales prone to recall bias and objective actigraphy, which captures sex-specific sleep fragmentation. Conclusions. PA functions as an effective, non-pharmacological stabilizer of sleep profiles by regulating physiological mechanisms and modulating cognitive-behavioral vulnerabilities. Future research must prioritize longitudinal designs pairing subjective metrics with high-resolution wearable actigraphy to establish precise, age-specific dose-response recommendations.